ON ONE CONTINUED ACT IN TAX CRIME IN INDONESIA - Denny Irawan (Scientia Integritas Utama, 2022)
Delicts in criminal acts in the field of taxation comply with the lex specialis derogate legi generali principle of the Criminal Code (KUHP) and are included in complex criminal acts in their implementation. Given the violation of criminal acts and there are several offenses in criminal acts of taxation, it is necessary to consider the concept of renewal of a continuing action (one further action) in criminal acts in the field of taxation with the obligation of investigators and public prosecutors to produce case files and indictments that are accurate, clear, and right, which results in the amount or accumulation of imprisonment and fines against a suspect or taxpayer in a fair, legal and efficient manner. Based on the normative juridical method, this study produces two conclusions. First, one follow-up law that has not been regulated directly in criminal provisions in the field of taxation is still under general criminal offenses, namely Article 64 paragraph (1) of the Criminal Code. Second, the concept (law) of follow-up action is needed in criminal acts in the field of taxation in Indonesia to be fair to accusations or taxpayers who commit violations and provide legal certainty and legal effectiveness to tax investigators in handling tax crimes which are complex and required to deal with cases carefully, clearly and completely